(untitled) - Weast, Robert C. (New York, 1974)
From science fair entrants to Nobel laureates, researchers around the world depend upon having access to authoritative, up-to-date data. And for nearly 90 years, they have relied on the CRC Handbook of Chemistry and Physics for that data.This year is no exception. New tables, extensive updates, and added sections mean the Handbook has once again set a new standard for reliability, utility, and thoroughness.Outstanding features of the 83rd edition:·Standard Thermodynamic Properties of Chemical Substances-Thoroughly revised with new substances and updated values·Ionization constants for buffers used in biological research-Definitive data that allow the correct interpretation of experiments·Directory of Physical and Chemical Data Sources-A selective listing of the most reliable sources of physical and chemical properties data, including data journals, data centers, major handbooks, and Internet sites ·Atomic weights-Updated with the latest changes adopted by IUPAC in 2001Other refinements and new topics include:·Atomic and Molecular Polarizabilities Updated·Characteristic Bond Lengths in Free Molecules New!·Correction of Barometer Readings to 0°C Temperature New!·Electron AffinitiesUpdated·Eutectic Temperatures of Low-Melting Alloys New!·Nuclear Spins and Moments for NMR Spectroscopy Updated·Permittivity of Water as a Function of Temperature and Pressure New!·Sensitivity of the Human Eye to Light of Different Wavelengths New!·Thermodynamic Functions and RelationsNew!·Vapor Pressure of Mercury New!·Viscosity and Density of Concentrated Hydroxide Solutions New!·Viscosity of Liquid Metals New!
Keywords: Chemistry,Physics,Hóa học,Vật lý học